The Evangelical Puzzle Partially Explained: Privileged Prejudice and the Development of Appreciative Attitudes Toward Evangelical Christianity - Mayhew, Matthew J.; Winkler, Christa E.; Staples, B. Ashley; Singer, Kevin; Shaheen, Musbah; Rockenbach, Alyssa N. (Frontiers in Education, 2022)
Background: Identifying the hallmarks of an evangelical Christian is a frequent focus for news outlets, commentators, and researchers seeking to understand the United States in the era of and following the Trump presidency. Evangelical Christian college students often simultaneously hold the privileges that accompany dominant religious identities and the silencing that come with expressing them on college campuses. Consistently and empirically, the college campus has been shown to foster individuals’ appreciative attitudes towards students holding different religious and non-religious worldviews. Yet, no studies have investigated evangelical Christian appreciation developmentally over four years of college using a mixed-methods approach for doing so. Purpose: This mixed-methods inquiry examined how college students grew in appreciation of evangelical Christians across four years of college. Methods: This paper used data gathered through the Interfaith Diversity Engagement and Attitudes Longitudinal Survey (IDEALS), a nationally-representative, mixed-methods study that included survey data collection from 9,470 students at 122 colleges and universities over three time points, and 18 qualitative case studies conducted across institutions of various sizes, locations, and affiliations. Results: Using latent growth modeling, we demonstrate that overall appreciation for evangelicals grows during college and is related to religiously-inclusive campus climates and institutional cultures that invite and embrace worldview diversity. Related qualitative insights punctuate that stories of change in evangelical appreciation tend to center on personal relationships with evangelicals, efforts to understand evangelical viewpoints, and a recognition that Christian students may have the privilege of operating from unexamined beliefs. Conclusion and Implications: Study results provide concrete quantifiable educational practices that educators could use to support student growth from tolerance to appreciation for the ethical and societal contributions of their evangelical peers.